2015
DOI: 10.1007/s13337-015-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous interferon prolongs survival of rabies infected mice

Abstract: Rabies is an acute viral infection that causes encephalomyelitis in almost all warm blooded animals and is invariably fatal once the clinical signs appear. The present study was carried out to assess the effect of recombinant human interferon alpha (rhIFN a-2A) treatment on the survival of rabies infected mice and its correlation with cytokines expression. The gene expression of TNF-a and IL-6 was measured by SYBR Green Real Time PCR for two groups-''Pre-exposure'' (mice were inoculated with rhIFN a-2A prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Treatment with recombinant human interferon alpha (rhIFN a¡2A) in rabies infected mice resulted in delayed mortality and significantly reduced expression of TNF-a and IL-6 both in the pre-exposure and post-exposure groups. These findings suggested that regulation of cytokine secretion using exogenous cytokines may offer novel therapeutic approaches for the treatment of rabies (Mehta et al 2015). Recombinant RABVs expressing the NanoLuc luciferase (NanoLuc) system facilitates screening of small molecules for inhibition of RABV infection (Anindita et al 2016).…”
Section: Theraputic Approachesmentioning
confidence: 99%
“…Treatment with recombinant human interferon alpha (rhIFN a¡2A) in rabies infected mice resulted in delayed mortality and significantly reduced expression of TNF-a and IL-6 both in the pre-exposure and post-exposure groups. These findings suggested that regulation of cytokine secretion using exogenous cytokines may offer novel therapeutic approaches for the treatment of rabies (Mehta et al 2015). Recombinant RABVs expressing the NanoLuc luciferase (NanoLuc) system facilitates screening of small molecules for inhibition of RABV infection (Anindita et al 2016).…”
Section: Theraputic Approachesmentioning
confidence: 99%
“…Elevated TNF-α and IL-6 levels are found in the serum and the cerebrospinal fluid of patients and have been correlated with disease severity and mortality in cases of JE, Parkinson syndrome, and Alzheimer disease [49,50] . The downregulation of TNF-α genes has also been reported during protection elicited by recombinant human IFN-α-2a treatment in a urine model of rabies [51] .…”
Section: Discussionmentioning
confidence: 80%
“…The aim of the study was to investigate the effect of giving exogenous cytokines to influence the endogenous cytokines. This approach of treatment could mild the symptoms, delay the death and increase the number of survivals [85] , [86] . The development of NanoLuc luciferase (NanoLuc) molecules enabled screening of intracellular molecules which can inhibit RABV infection.…”
Section: Advances In Rabies Prevention and Treatmentmentioning
confidence: 99%